Comparative analysis of two optimal design approaches of PM disc motor for EV - Cvetkovski, Goga; Petkovska, Lidija; Gair, Sinclair (IEEE, 2010)
The application of the permanent magnet disc motor (PMDM) is in electric vehicle and therefore there are several objectives that could be tackled in the design procedure, such as an increased efficiency, reduced total weight of the motor or increased power/weight ratio (specific power). In this paper an optimal design of a PMDM using efficiency and specific power as objective function is performed. In the design procedure performed on the PM disc motor, genetic algorithm, as an optimisation tool is used. Comparative analysis of the optimal motor solutions and its parameters in relation to the initial model is presented.
Keywords: Efficiency, Design of Permanent magnet motor, Electric vehicle.